Impact of histone deacetylase inhibitor valproic acid on the anticancer effect of etoposide on neuroblastoma cells - Groh, Tomas; Hrabeta, Jan; Poljakova, Jitka; Eckschlager, Tomas; Stiborova, Marie (Neuro endocrinology letters, 2012)
OBJECTIVES: Etoposide (Vepesid, VP-16), an inhibitor of topoisomerase II, is a chemotherapeutic drug commonly used for treatment of different types of malignant diseases. By inhibiting the topoisomerase II enzyme activity in cancer cells, this drug leads to DNA damage and subsequently to cell death. In this study, we investigated the effect of this anticancer drug alone and in combination with a histone deacetylase (HDAC) inhibitor, valproic acid (VPA), on a human UKF-NB-4 neuroblastoma cell line. METHODS: The effects of etoposide and VPA on UKF-NB-4 cells were tested under the normoxic and also the hypoxic (1% O2) cultivation conditions. The cytotoxicity of etoposide and VPA to a UKF-NB-4 neuroblastoma cell line was evaluated with MTT assay. Apoptosis of the cells was analyzed by flow cytometry using an Annexin V and propidium iodide binding method. The effect of etoposide and VPA on the cell cycle distribution was determined by flow cytometric analysis using propidium iodide staining. RESULTS: The results of the study demonstrate that UKF-NB-4 neuroblastoma cells are sensitive both to etoposide and to VPA. They also indicate that the impact of VPA on cytotoxicity of etoposide in these tumor cells varies depending on the sequence of cultivation of the cells with the drugs. As a suitable sequence of cultivation, with a high rate of suppression of neuroblastoma cell growth was found the preincubation of the cells with etoposide, which was followed by their cultivation with VPA. In contrast, the reversed combination (preincubation of the cells with VPA before their treating with etoposide) did not give any increase in etoposide cytotoxicity. The effect of such combined treatment can be explained by measuring the cell cycle distribution, which shows that both etoposide and VPA change the cell cycle phase distribution. CONCLUSION: Etoposide and VPA were found as cycle phase specific drugs that are cytotoxic to human UKF-NB-4 neuroblastoma cells used either as single drugs or both together. However, whereas VPA might sensitize the cells to etoposide, inappropriate sequence of cultivation of the cells with VPA can decrease the etoposide cytotoxic efficacy. The results found here warrant further studies of combined treatment of neuroblastoma cells with etoposide with HDAC inhibitors and may help in the design of new protocols geared to the treatment of high risk neuroblastomas.
Keywords: nádory mozku; Valproic Acid; Antineoplastic Agents, Phytogenic; Humans; Histone Deacetylase Inhibitors; neuroblastom; etoposid; fytogenní protinádorové látky; Brain Neoplasms; Cell Cycle; rizikové faktory; Drug Synergism; nádory kostní dřeně; Etoposide; lidé; chemorezistence; synergismus léků; apoptóza; Bone Marrow Neoplasms; inhibitory histondeacetylas; nádorové buněčné linie; Neuroblastoma; Cell Line, Tumor; buněčný cyklus; Drug Resistance, Neoplasm; Apoptosis; kyselina valproová; Risk Factors